Handbook of research on business models in modern competitive scenarios - Jamil, George Leal, 1959- (Business Science Reference, 2019)
"This book explores how business models are conceptualized, studied, designed, implemented and, in the end, how they can be improved. It also discusses how business models contribute for strategic competition in this new era, of technological and social fast changes"--